Scientific substantiation of the state's economic policy in agriculture: theoretical foundations - Migunovand Rishat A.; Syutkina Anastasia A. (BIO Web of Conferences, 2023)
The work is devoted to the complex issues of the effect of the theoretical prerequisites of state policy, the interaction of the market and the state on the sustainable development of the agricultural sector. The purpose of the work is to substantiate the scientific theoretical foundations of the state's economic policy in the agricultural sector. The methodological basis of the study is an integrated approach, in which the scientific foundations of the state economic policy, including agrarian policy are considered. The study of the fundamentals of the state economic policy from the point of view of the categories that determine its economic structure – "freedom" and "order", was conducted. It is shown that each theoretical doctrine has opportunities for its implementation in a specific historical period, when certain circumstances have developed for this; for greater efficiency of state regulation, a synthesis of applied theoretical models is necessary. The necessity of considering the cyclical development of agriculture in the state and market regulation of the industry, including the cycles of agri-food conjuncture development, is substantiated. The methods of agrarian policy of modern Russia of the II cycle are substantiated: the expansion of demand for food, the policy of increasing the competitiveness of the agricultural sector and the efficiency of domestic production.